Age can be a Problem: Clostridium difficile and Cytomegalovirus Colitis Coinfection in an Immunocompetent 90-year-old Patient - Po-Hsun Chen; I-Ta Lu; Bor-Jen Lee; Chen-Yu Wang; Chien-Kuan Lee (International Journal of Gerontology, 2015)
Clostridium difficile colitis and cytomegalovirus colitis coinfection has been documented in immunocompromised patients. However, this kind of coinfection has rarely been reported in immunocompetent patients. We present a 90-year-old, critically ill, immunocompetent patient, who had a C. difficile and cytomegalovirus colitis coinfection. Although the common risk factors of both types of colitis are well known, clinical physicians still need to be alert to this coinfection because severe complications of CMV colitis have been reported previously. Physicians should be more aggressive in the management of elderly immunocompetent patients with refractory symptoms of colitis.